(untitled) (Human Factors in Design, 2019)
The activities of maintenance and cleaning of swimming pools require several efforts and postures that could cause discomfort and injuries. In this way, this research aimed to identify, applying the OWAS method, the musculoskeletal disorders that affect these workers. The results obtained have made it possible to identify the risks and consequently actions to reduce or eliminate them. The most critical posture identified was the kneeling pose when he is brushing the sides of the swimming pool. To eliminate this posture, it is proposed to change a manual brush to a brush with telescopic stick, designed with an angle that allows the worker to stand upright without flexed his trunk while cleaning the pool. This change improves the working conditions, providing well-being and reducing as negative consequences.